Draft Annual Plan 1983-84 Volume II Government of Andhra Pradesh - Planning Commission (Planning Commission, 1983)
The basic idea of this Corporation has been to render services to NRIs in the matter of investing the resources in this State, for some time to come it will be difficult to quantify the value of these resources, much less to charge from them. To secure letters of intent, licences , permits and various other clearances including financial tie-ups from various agencies lot of log worksheet be done by the officers of this Corporation. It is difficult to charge the NRIs for these services , specially in the beginning.
Finance and Planning Department Government of Andhra Pradesh